Influence of Renal Function on Evolocumab Exposure, Pharmacodynamics, and Safety. Issue 3 (24th January 2019) - Lee, Edward; Gibbs, John P.; Emery, Maurice G.; Block, Geoffrey; Wasserman, Scott M.; Hamilton, Lisa; Kasichayanula, Sreeneeranj; Hanafin, Patrick; Somaratne, Ransi; Egbuna, Ogo
Abstract: We evaluated the pharmacokinetics, pharmacodynamics, and safety of evolocumab, a fully human monoclonal antibody against proprotein convertase subtilisin kexin type 9 (PCSK9), in an open‐label, parallel‐design study in participants with normal renal function (n = 6), severe renal impairment (RI; n = 6), or end‐stage renal disease (ESRD) receiving hemodialysis (n = 6) who received a single 140‐mg dose of evolocumab. The effects of evolocumab treatment on low‐density lipoprotein cholesterol (LDL‐C) lowering and unbound PCSK9 concentrations were similar in the normal renal function group and the renally impaired groups. Geometric mean Cmax and AUClast values in the severe RI and ESRD hemodialysis groups compared with the normal renal function group were lower but within 37% of the normal renal function group (Jonckheere‐Terpstra trend test; Cmax, P = .23; AUClast, P = .22) and within 26% after adjusting for body weight (mean body weight was approximately 9% higher in the renally impaired groups compared with the normal renal function group). No correlations were observed between exposure and baseline creatinine clearance. No adverse event was determined by the investigators to be related to evolocumab, and there were no trends indicative of clinically important effects on laboratory variables or vital signs. Overall, there were no meaningful differences in evolocumab exposure, as assessed by Cmax and AUClast, in patients with severe RI and ESRD hemodialysis compared with patients with normal renal function, and LDL‐C‐lowering effects were similar across groups. These results support the use of evolocumab without dose adjustment in patients who have severe RI or ESRD.